The role of dynamic capabilities in enhancing strategic sovereignty- An analytical study in the men’s clothing factory in Najaf AL Ashraf - Al-Hadrawi رافد حميد عباس; Mohammed رياض جواد; Hmoud عدنان رحيم; Salman زهير وسمي (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The research aimed at diagnosing the laboratory’s level of interest in the research variables (dynamic capabilities and strategic sovereignty), as well as testing the influence relationship between them. The research started from a problem represented by the weak strategic sovereignty as a result of the intense competition in the industrial sector. The research adopted the descriptive analytical approach by highlighting the intellectual and conceptual foundations of the research variables, and then adopting a questionnaire form to collect appropriate data and information from the research sample. The questionnaire included (27) items, with (12) items for the dynamic capabilities variable and (15) items for the strategic sovereignty variable. Was chosen a random sample of workers in the men’s clothing factory in Najaf Ashraf, numbering (152) individuals, and the research put four hypotheses that were tested on the ready-made statistical program (SMART pls. The research reached a number of conclusions, the most important of which is the presence of a clear weakness on the part of the laboratory in the strategic sovereignty, and also the research concluded that the dynamic capabilities have a positive impact and contribute effectively to strengthening strategic sovereignty, but after the acquisition it does not support the strategic sovereignty in the laboratory. The research recommended the need to increase attention to strategic sovereignty and to replace the adopted methods of acquisition with other more effective methods.